Green Tea Daily Consume Reduced Free Radicals on Moderate Smokers - Rosyanne Kushargina; Rimbawan Rimbawan; Budi Setiawan (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2018)
Smoking can enhance free radicals on blood plasma. Many previous studies proved that tea is a source of antioxidants which might reduce free radicals. Green tea is known to have the higher antioxidant capacity compared to black tea. This study aims to analyze the effect of green tea on reduction of free radicals on moderate smokers, using a pre-post experimental design. Green tea infusions were prepared with commercially available dried tea leaves (Green Tea Gamboeng Series) from the Research Centers of Tea and Cinchona Gambung, West Java. Nine moderate smokers (11-21 cig/day) aged 30-45 years were instructed to drink 200 ml green tea three times a day for four weeks. Total Antioxidant Capacity (TAC) of blood serum was measured at baseline and after four weeks intervention period. The level of TAC significantly increased from 1.18 m mol/L to 1.34 m mol/L after four weeks intervention (P=0.000). These results prove that drinking 200 ml of green tea three times a day for four weeks has a significant benefit reducing free radicals of moderate smokers. Moderate smokers are advised to consume green tea continuously to sustain these positive effects.